Herbivory and Drought Reduce the Temporal Stability of Herbaceous Cover by Increasing Synchrony in a Semi-arid Savanna - Ebel, Carmen R.; Case, Madelon F.; Werner, Chhaya M.; Porensky, Lauren M.; Veblen, Kari E.; Wells, Harry B. M.; Kimuyu, Duncan M.; Langendorf, Ryan E.; Young, Truman P.; Hallett, Lauren M. (Frontiers in Ecology and Evolution, 2022)
Ecological stability in plant communities is shaped by bottom-up processes like environmental resource fluctuations and top-down controls such as herbivory, each of which have demonstrated direct effects but may also act indirectly by altering plant community dynamics. These indirect effects, called biotic stability mechanisms, have been studied across environmental gradients, but few studies have assessed the importance of top-down controls on biotic stability mechanisms in conjunction with bottom-up processes. Here we use a long-term herbivore exclusion experiment in central Kenya to explore the joint effects of drought and herbivory (bottom-up and top-down limitation, respectively) on three biotic stability mechanisms: 1) species asynchrony, in which a decline in one species is compensated for by a rise in another, 2) stable dominant species driving overall stability, and 3) the portfolio effect, in which a community property is distributed among multiple species. We calculated the temporal stability of herbaceous cover and biotic stability mechanisms over a 22-year time series and with a moving window to examine changes through time. Both drought and herbivory additively reduced asynchronous dynamics, leading to lower stability during droughts and under high herbivore pressure. This effect is likely attributed to a reduction in palatable dominant species under higher herbivory, which creates space for subordinate species to fluctuate synchronously in response to rainfall variability. Dominant species population stability promoted community stability, an effect that did not vary with precipitation but depended on herbivory. The portfolio effect was not important for stability in this system. Our results demonstrate that this system is naturally dynamic, and a future of increasing drought may reduce its stability. However, these effects will in turn be amplified or buffered depending on changes in herbivore communities and their direct and indirect impacts on plant community dynamics.